Correction: An Improved Transplantation Strategy for Mouse Mesenchymal Stem Cells in an Acute Myocardial Infarction Model - Jin, Jianliang; Zhao, Yingming; Tan, Xiao; Guo, Chun; Yang, Zhijian; Miao, Dengshun (PLOS ONE, 2024)
null